2021
DOI: 10.1021/acs.bioconjchem.1c00271
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Intrinsically Radiolabeled Poly(lactic-co-glycolic acid) Nanoparticles for ex Vivo Autologous Cell Labeling and in Vivo Tracking

Abstract: With the advent of novel immunotherapies, interest in ex vivo autologous cell labeling for in vivo cell tracking has revived. However, current clinically available labeling strategies have several drawbacks, such as release of radiolabel over time and cytotoxicity. Poly(lactic- co -glycolic acid) nanoparticles (PLGA NPs) are clinically used biodegradable carriers of contrast agents, with high loading capacity for multimodal imaging agents. Here we show the development of PLGA-based NPs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In our previous work, we have shown that poly(lactic-co-glycolic acid) NPs with amine groups (PLGA-NH 2 NPs) can be used to radiolabel cells and demonstrates improved radiolabel retention compared with the oxine labeling method [31]. Here, we report the intrinsic labeling capacity of these NPs with [ 89 Zr]ZrCl 4 under various conditions.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…In our previous work, we have shown that poly(lactic-co-glycolic acid) NPs with amine groups (PLGA-NH 2 NPs) can be used to radiolabel cells and demonstrates improved radiolabel retention compared with the oxine labeling method [31]. Here, we report the intrinsic labeling capacity of these NPs with [ 89 Zr]ZrCl 4 under various conditions.…”
Section: Introductionmentioning
confidence: 93%
“…The same preparation protocol was used as described before [31]. Briefly, 100 mg of poly(lactic-co-glycolic acid) diamine endcap copolymer (PLGA-NH 2 , Mn = 5000, Sigma-Aldrich, Merck, Saint Louis, MO, USA), 200 µL of poly(propylene glycol) (PPO, 50 mg/mL stock, Sigma-Aldrich, average Mn 2700) and 900 µL perfluoro-15-crown-5-ether (PFCE, Exfluor Inc., Round Rock, TX, USA) were dissolved in 3 mL dichloromethane (DCM, Merck, Darmstadt, Germany).…”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations